Changes in the TBARs content and superoxide dismutase, catalase and glutathione peroxidase activities in the lymphoid organs and skeletal muscles of adrenodemedullated rats - Pereira,B. (1998)
Thiobarbituric acid reactant substances (TBARs) content, and the activities of glucose-6-phosphate dehydrogenase (G6PDh), citrate synthase (CS), Cu/Zn- and Mn-superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPX) were measured in the lymphoid organs (thymus, spleen, and mesenteric lymph nodes (MLN)) and skeletal muscles (gastrocnemius and soleus) of adrenodemedullated (ADM) rats. The results were compared with those obtained for sham-operated rats. TBARs content was reduced by adrenodemedullation in the lymphoid organs (MLN (28%), thymus (40%) and spleen (42%)) and gastrocnemius muscle (67%). G6PDh activity was enhanced in the MLN (69%) and reduced in the spleen (28%) and soleus muscle (75%). CS activity was reduced in all tissues (MLN (75%), spleen (71%), gastrocnemius (61%) and soleus (43%)), except in the thymus which displayed an increment of 56%. Cu/Zn-SOD activity was increased in the MLN (126%), thymus (223%), spleen (80%) and gastrocnemius muscle (360%) and was reduced in the soleus muscle (31%). Mn-SOD activity was decreased in the MLN (67%) and spleen (26%) and increased in the thymus (142%), whereas catalase activity was reduced in the MLN (76%), thymus (54%) and soleus muscle (47%). It is particularly noteworthy that in ADM rats the activity of glutathione peroxidase was not detectable by the method used. These data are consistent with the possibility that epinephrine might play a role in the oxidative stress of the lymphoid organs. Whether this fact represents an important mechanism for the establishment of impaired immune function during stress remains to be elucidated.